Compost from organic waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Composting of biodegradable wastes (household rubbish, organic wastes) for use in the field and garden is a good way to maintain biological activity in the soil and protect the environment. Anyone can produce good quality compost from wastes. The...